(untitled) (Società e diritti, 2017)
The promotional function of law in crisis with the crisis of Kelsen normativism. The claim formalist can not found a purpose not hierarchically higher regulated directions within the legal system. This "failure" was analyzed by Sergio Cotta which proposed the onto phenomenological analysis of the legal basis as a possible way out to rediscover the meaning of legal structure. Key words: promotional function, philosophy of law, natural law